Penerapan ISO 31000:2018 untuk Analisis Manajemen Risiko pada Sistem Informasi Smart Operation di PT. XYZ - Jericho, J; Haryani, Endang (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
This study objectives to analyze risk management on the Information System of Smart Operation at PT. XYZ, through identifying risks, describing the impact of these risks, and recommending risk treatment. This system manages sales transactions, from sales orders to financial reporting. This study is driven by the importance of information technology investment to improve a company’s efficiency. However, this investment has uncertainties about the values that can be attained and the risks that may occur. The research applied a qualitative method and ISO 31000:2018 as the referred framework. The analysis identified 12 risks in the 5 sectors. The research found that there is no high-level risk, 8 medium-level risks and 4 low-level risks. Based on these findings, the study concludes that related to the implementation of the information system, there are no risks that endanger and harm the company. Based on the risk impact, the recommended risk treatment is to mitigate or reduce risks. There are 4 medium risks that have the greatest score of 6, among others are order recording errors, number of goods decrease, accidental loss of goods/theft, and wrong goods selection. Actions to reduce the risk are regular log checking, training on the use of applications, regular stock-opname, placing goods within CCTV range and rechecking documents with goods sent. Meanwhile, the risk of counterfeit money has the least score of 1, because the company has an accurate detection device